Archaeometallurgy - materials science aspects - Hauptmann, Andreas (Springer, 2020)
This book successfully connects archaeology and archaeometallurgy with geoscience and metallurgy. It addresses topics concerning ore deposits, archaeological field evidence of early metal production, and basic chemical-physical principles, as well as experimental ethnographic works on a low handicraft base and artisanal metal production to help readers better understand what happened in antiquity. The book is chiefly intended for scholars and students engaged in interdisciplinary work
Keywords: Archäologie; Metallurgie; Geochemistry; Mineral resources; Archaeology; Materials science